The impact of participatory plant breeding (PPB) on landrace diversity: A case study for high-altitude rice in Nepal - Joshi, Krishna D.; Sthapit, B.R.; Witcombe, John R. (CGIAR Systemwide Program on Participatory Research and Gender Analysis for Technology Development and Institutional Innovation, 2001)
Participatory plant-breeding (PPB) methods were used to develop two acceptable, cold-tolerant rice varieties in Nepal: Maehhapuchhre-3 (M-3) and Machhapuchhre-9 (M-9). Both were derived from the cross Fuji 102 Chhomrong Dhan. Following the introduction of these varieties from 1993 to 1998,the changes in the rice landraces and varieties that fanners grew were studied in 10 villages. In seven of the villages, for which data were analyzed for both 1996 and 1999, fanners grew 19 landraces and four modem varieties, of which three (M-3, M-9, and Lumle 2) were the products of PPB. These three varieties covered 11 % of the total surveyed area in 1999. The introduction of the PPB varieties had the greatest impact on the more commonly grown landraces. During the years studied, because the new varieties had exotic germplasm in their parentage, there was an overall increase in varietal diversity. However, in the future, ¡increasing adaption of M-3 and M-9 could result in significant reductions in varietal diversity.